EFEK DAN KEBIASAAN MENDENGARKAN SIARAN RADIO MELALUI MOBILE APPLICATION: STUDI DESKRIPTIF PADA KOMUNITAS SHE AND FRIENDS - Setyowati, Ratna Indah; Sudaryanto, Edy; Satvikadewi, AAI. Prihandari (Universitas 17 Agustus 1945 Surabaya, 2015)
The development of communication technology, especially in the mass media made public with easyaccess to any information. No exception to the radio, with the creation of a mobile application that canbe freely downloaded through the Android-based mobile or IOS, the radio business people hope this canbe a tool that allows listeners to access radio anywhere and anytime. The emergence of new media andnew habits effect on the mass media. To meet these objectives, used in-depth interviews with communitymembers she and friends. This study uses the basic theory of mass media effects .And the result of thisresearch is that the effect occurs in members she and friends while listening to She Radio 99.6 FM viamobile application is the addition of listening to a radio broadcast schedule, causing a feeling of comfort,and a member of she and friends is also more positive about She Radio. Habits member she and friendsin listening to the radio using the mobile application is on average duration of 2 hours/day at a time andplace to listen to the broadcast that is between 6:00 to 10:00 o'clock pm in the House, between the hoursof 21:00 to 23:00 pm in the House, and in the Office the time between the hours of 11:00 to 16:00 o’clockpm. The main reason the replacement of the radio channel to another is due to the quality of She Radiomobile application is still not good enough (often die suddenly). And between the two features in additionto streaming radio, read the article a chaperone activity while listening to the radio, while the audience isreading the ad is to find information about the fashion show or exhibition.Keywords: mass media effect, habbit of listening radio, mobile application